Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physreve.96.059902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Aging Wiener-Khinchin theorem and critical exponents of 1/fβ noise [Phys. Rev. E 94 , 052130 (2016)]

Abstract: This corrects the article DOI: 10.1103/PhysRevE.94.052130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 1 publication
1
38
0
Order By: Relevance
“…Models of such nonstationary behavior are found in the theory of glasses [17,18], blinking quantum dots, analytically and experimentally [8,14], nanoscale electrodes [19], and interface fluctuations in the (1+1)-dimensional KPZ class, both experimentally and numerically, using liquid-crystal turbulence [20]. Thus one school of thought supports the idea that the sample spectrum exhibits nonstationary features of a particular kind [16,19,[21][22][23]. However, the others argue that while Mandelbrot's nonstationarity scenario is theoretically elegant, it is not a universal explanation since it is backed only by several experiments [8,19,20], and the spectrum is stationary [2,4,5].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Models of such nonstationary behavior are found in the theory of glasses [17,18], blinking quantum dots, analytically and experimentally [8,14], nanoscale electrodes [19], and interface fluctuations in the (1+1)-dimensional KPZ class, both experimentally and numerically, using liquid-crystal turbulence [20]. Thus one school of thought supports the idea that the sample spectrum exhibits nonstationary features of a particular kind [16,19,[21][22][23]. However, the others argue that while Mandelbrot's nonstationarity scenario is theoretically elegant, it is not a universal explanation since it is backed only by several experiments [8,19,20], and the spectrum is stationary [2,4,5].…”
Section: Introductionmentioning
confidence: 75%
“…Mandelbrot suggested that 1/f α power spectrum ages which means that S t (ω) ∝ ω −2+β t −1+β , so α = 2−β [13]. Importantly, here the spectrum depends on the measurement time t (see details below), and the total power remains finite ∞ 1/t S t (ω)dω = const [14,16]. The time dependent amplitude of S t (ω) provides a normalizable spectral density, therefore it should naturally appear in a bounded process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this subject is related to 1/f noise, it still has aroused widespread interest. By using CTRW formalism one can focus on the origin of 1/f noise, something that was known for a while [42,43] (see also some remarks below).…”
mentioning
confidence: 99%